2020
DOI: 10.21203/rs.3.rs-58186/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of COVID-19 on Anxiety, Depression and Other Mental Health Issues: A worldwide scope review.

Abstract: BACKGROUND: The COVID-19 pandemic has spread across the world and, along with it, a considerable degree of fear and uncertainties that impact on various aspects of societal life, including on people’s Mental Health (MH). Understanding how the COVID-19 pandemic affects MH can help to implement interventions and adequate public policies, providing more effective responses to mitigate its effects.OBJECTIVES: To summarize the scientific evidence on the possible influence of the Covid-19 pandemic on MH, critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…Increased anxiety, apart from fear, symptoms of depression, and lower quality of sleep, was the most frequently reported mental consequence of the COVID-19 pandemic in the general population [75][76][77]. Similar findings were confirmed for health care professionals [78] and patients who had suffered from the symptoms of COVID-19 infection [79].…”
Section: Discussionsupporting
confidence: 61%
“…Increased anxiety, apart from fear, symptoms of depression, and lower quality of sleep, was the most frequently reported mental consequence of the COVID-19 pandemic in the general population [75][76][77]. Similar findings were confirmed for health care professionals [78] and patients who had suffered from the symptoms of COVID-19 infection [79].…”
Section: Discussionsupporting
confidence: 61%
“…This occurrence was likely the result of the demographic composition of the colleges and departments targeted for recruitment [ 119 ]. Selection bias related to which students participated in the study questionnaire based on interest and access/availability is also possible [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies support that the conclusion that the novel coronavirus (SARS-CoV-2) and its corresponding disease (COVID- 19) have dramatically impacted people's mental health and behavior [1][2][3][4][5], with very few studies suggesting otherwise [6]. Mental health hotlines in the United States experienced 1,000% increases during the month of April, when most people were under lockdown because of the pandemic [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States the COVID-19 Impact Survey found that 34.4% of households with children ≤ 12 years old were food insecure in April 2020, compared with 15.1% in 2018 (7) . Further, multiple studies have found that the COVID-19 pandemic and lockdowns have negatively affected mental health in diverse contexts and populations (8,9) . Nevertheless, evidence on food insecurity and mental health in LMICs, particularly in Latin America, that compares rates before and during the pandemic are limited.…”
Section: Introductionmentioning
confidence: 99%